Landscape and anthropogenic features influence the use of auditory vigilance by mule deer. (11th September 2014) - Lynch, Emma; Northrup, Joseph M.; McKenna, Megan F.; Anderson, Charles R.; Angeloni, Lisa; Wittemyer, George
Lay summary: Using on-animal acoustical monitoring to study the behavior of terrestrial animals, we examine how the use of auditory vigilance in mule deer varies with landscape features. Deer used this antipredator strategy more when in forested cover and at night, where visual vigilance was likely to be less effective. Abstract : While visual forms of vigilance behavior and their relationship with predation risk have been broadly examined, animals also employ other vigilance modalities such as auditory vigilance by listening for the acoustic cues of predators. Similar to the tradeoffs associated with visual vigilance, auditory behavior potentially structures the energy budgets and behavior of animals. The cryptic nature of auditory vigilance makes it difficult to study, but on-animal acoustical monitoring has rapidly advanced our ability to investigate behaviors and conditions related to sound. We utilized this technique to investigate the ways external stimuli in an active natural gas development field affect periodic pausing by mule deer ( Odocoileus hemionus ) within bouts of rumination-based mastication. To better understand the ecological properties that structure this behavior, we investigate spatial and temporal factors related to these pauses to determine if results are consistent with our hypothesis that pausing is used for auditory vigilance. We found that deer paused more when in forested cover and at night, where visual vigilance was likely to be less effective. Additionally, deer paused more in areas of moderate background sound levels, though responses to anthropogenic features were less clear. Our results suggest that pauses during rumination represent a form of auditory vigilance that is responsive to landscape variables. Further exploration of this behavior can facilitate a more holistic understanding of risk perception and the costs associated with vigilance behavior.